2007
DOI: 10.1002/pola.22038
|View full text |Cite
|
Sign up to set email alerts
|

Novel analytical method for the crosslinking process: Infrared thermographic analysis of the thermally latent cationic polymerization of a spiroorthoester and a bifunctional oxetane for the construction of a low‐shrinkage curing system

Abstract: Thermal behaviors were monitored by infrared thermographic analysis in the copolymerization of a spiroorthoester and a bifunctional oxetane with thermally latent initiators [benzyl tetrahydrothiophenium hexafluoroantimonate (BTHT) and benzyl 4-hydroxyphenyl methyl sulfonium hexafluoroantimonate (BPMS)]. The copolymerization with BPMS increased the temperature during the copolymerization more than that with BTHT, whereas the exothermicities were lowered with the increase in the initial feed ratio of the spiroor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Oxetane has a four‐membered cyclic ether ring and the basicity of its oxygen atom is higher than that of other cyclic ethers, such as epoxide (three‐membered ring), tetrahydrofuran (five‐membered ring), or tetrahydropyran (six‐membered ring) 1. Because of the high basicity, the cationic polymerization of oxetanes proceeds smoothly to afford high‐molecular polyethers in good yields 2–13. Cationic isomerizations of oxetanes with ester, amide, and imide moieties were also reported 14–19.…”
Section: Introductionmentioning
confidence: 99%
“…Oxetane has a four‐membered cyclic ether ring and the basicity of its oxygen atom is higher than that of other cyclic ethers, such as epoxide (three‐membered ring), tetrahydrofuran (five‐membered ring), or tetrahydropyran (six‐membered ring) 1. Because of the high basicity, the cationic polymerization of oxetanes proceeds smoothly to afford high‐molecular polyethers in good yields 2–13. Cationic isomerizations of oxetanes with ester, amide, and imide moieties were also reported 14–19.…”
Section: Introductionmentioning
confidence: 99%
“…IR thermography revealed that the addition of PSOE suppressed temperature increases during polymerization, which would lead to thermal runaway and thermal shrinkage. Polymer networks were obtained from the curing reaction of the bifunctional oxetane 1,4-bis(3-ethyloxetanylmethoxy)benzene with PSOE in the ratio of 80:20 with volumetric expansion of 3.7 vol.% [ 77 ].…”
Section: Expanding Oxacyclesmentioning
confidence: 99%
“…In addition, trialkyl aluminum/H 2 O catalytic system gives polyoxetanes with well‐controlled molecular weights . Oxetane monomers also undergo cationic ring‐opening copolymerization with six‐ or seven‐membered heterocyclic compounds such as tetrahydropyran, ε ‐caprolactone, 1,3,2‐dioxathiepane‐2‐oxide, spiroorthoester, and spiroorthocarbonate . In other ring‐opening copolymerizations, linear aliphatic polycarbonate synthesis by coupling of carbon dioxide (CO 2 ) and oxetane monomers is one of the important process because CO 2 is regarded as a cheap and green C1 resource, which is useful especially for phosgene free processes .…”
Section: Introductionmentioning
confidence: 99%